To solve for x, we first simplify the equation:
-4(3x + 10) - 2 = 54
Multiplying -4 by each term inside the parentheses, we get:
-12x - 40 - 2 = 54
Combining like terms, we have:
-12x - 42 = 54
Next, we add 42 to both sides of the equation:
-12x = 96
Finally, we divide both sides by -12 to isolate x:
x = 96 / -12
Simplifying the expression, we have:
x = -8
Therefore, x equals -8.
Solve for x: −4(3x+10)−2=54.(1 point)%0D%0AResponses%0D%0A%0D%0Ax=−4%0D%0A x equals negative 4%0D%0A%0D%0Ax=4%0D%0A x equals 4%0D%0A%0D%0Ax=−8%0D%0Ax equal negative 8%0D%0A%0D%0Ax=8%0D%0A x equals 8%0D%0ASkip to navigation%0D%0AHighlight%0D%0A%0D%0Apage 12 of 12
1 answer